The Presence of Gueada and Geada in the Place Names Featured in José de Villarroel’s Diccionario nomenclatór (1810) - Sánchez Rei, Xosé Manuel (Madrygal. Revista de Estudios Gallegos, 2025)
José de Villarroel’s Diccionario nomenclatór (1810) is a catalogue of names of the main sites and centres of population in Galicia at the start of the nineteenth century; one of his main models was the Bernardo Espinault Garcia’s Direccion General de Cartas en Forma de Diccionario (1775). Published prior to the standardisation of Galician, at a time when place names were transcribed according to Spanish orthographic conventions, the work reveals the presence of a number of popular, dialectal features of Galician among the items listed. Two of these, the voiced, back occlusive gueada and the normally voiceless, fricative geada phenomenon, are observed in some place names, reflecting local and/or structural forms of pronunciation still found in the language spoken in those areas today. This article examines the presence of these two apparent variants in the place names featured in Villarroel’s Diccionario nomenclatór, and their equivalent pronunciation and rendering today.
Keywords: Gueada; Geada; Galician; José de Villarroel; Place Names; Dialectal Variants